Pengaruh Stabilitas Sampel Darah EDTA Terhadap Pemeriksaan Hemoglobin dan Hematokrit pada Karyawan Puskesmas Kedung II Metode Otomatis - Anjani, Anisa Ayu; Hartinah, Dewi; Kurnia, Shinta Dwi; Rusidah, Yunita; Saputro, Arief Adi (Jaringan Laboratorium Medis, 2025)
This study aims to determine the effect of EDTA blood sample stability on hemoglobin (Hb) and hematocrit (Ht) examination results using an automatic method. EDTA blood samples from 38 employees of Kedung II Public Health Center were examined immediately (0 hours), after a 1-hour delay at room temperature (17–210C), and after a 1-hour delay in a refrigerator (2–80C). The results were analyzed using a Two-Way ANOVA test. The study showed no significant differences in hemoglobin and hematocrit levels between the three storage conditions (ρ 0.05). The average hemoglobin levels were 12.834 g/dL at 0 hours, 12.797 g/dL after 1 hour at room temperature, and 12.829 g/dL after 1 hour in the refrigerator. The average hematocrit levels were 38.484% at 0 hours, 38.321% after 1 hour at room temperature, and 38.434% after 1 hour in the refrigerator. The conclusion of this study is that storing EDTA blood samples for 1 hour, whether at room temperature or in the refrigerator, does not significantly affect hemoglobin and hematocrit examination results.